Comment on "High-temperature superconductivity in transition metallic hydrides MH11 (M = Mo, W, Nb, and Ta) under high pressure" by M. Du, Z. Zhang, H. Song, H. Yu, T. Cui, V. Z. Kresinc and D. Duan, Phys. Chem. Chem. Phys., 2021, 23, 6717. Issue 3 (10th January 2022) - Zheng, X. H.; Zheng, J. X.
Abstract : In superconductors, scattered electrons cover the entire surface of the Fermi sphere (circle in the figure, valency = 3). In the MP scheme in the article concerned, the shaded wedge confines coverage, causing errors in results. Abstract : The Monkhorst–Pack scheme is applied in Phys. Chem. Chem. Phys., 2021, 23, 6717 to study superconductivity in transition metallic hydrides, implying that umklapp phonons have been excluded. But in a superconductor scattered electrons should be able to cover the entire Fermi surface so that umklapp phonons must be included. The authors should take care to explain if and how measures were taken to include umklapp phonons for electron–phonon scattering.